Current safety issues with quadrivalent meningococcal conjugate vaccines - Tanya R. Myers; Michael M. McNeil (Taylor & Francis Group, 2018)
Invasive meningococcal disease, although rare, can present as sudden, life-threatening disease with high risk of mortality or severe long-term sequelae. The main prevention strategy for invasive meningococcal disease in the United States is the routine vaccination of adolescents and other persons at increased risk of meningococcal disease with quadrivalent meningococcal conjugate vaccines. Two such vaccines are currently licensed and available in the United States, Menactra® (Sanofi Pasteur) and Menveo® (GlaxoSmithKline), and usage in the adolescent population has steadily increased since their introduction. Although early reports raised concerns about a possible association of Menactra with Guillain-Barré syndrome, a comprehensive safety review determined that if such risk existed it was no more than 0.66 cases per 1 million vaccinations. More recently, a study found an elevated risk of Bell's palsy when Menveo was administered concomitantly with other vaccines but no association was found when the vaccine was administered alone. In this commentary, we describe the current state of knowledge with respect to the safety of quadrivalent meningococcal conjugate vaccines, and we identify potential areas for safety research for these vaccines.